Acute bacterial meningitis in Iran: Systematic review and meta-analysis. - Hamidreza Houri; Ali Pormohammad; Seyed Mohammad Riahi; Mohammad Javad Nasiri; Fatemeh Fallah; Hossein Dabiri; Ramin Pouriran (PLoS ONE, 2017)
Introduction Bacterial meningitis persists in being a substantial cause of high mortality and severe neurological morbidity, despite the advances in antimicrobial therapy. Accurate data has not been available regarding the epidemiology of bacterial meningitis particularly in developing countries, yet. Indeed, the present systematic review provides a comprehensive data analysis on the prevalence and epidemiology of bacterial meningitis in Iran. Methods We systematically reviewed articles from 1994 to 2015. The reports which contained the prevalence and etiology of acute bacterial meningitis by valid clinical and laboratory diagnosis were comprised in the present study. Results Our analysis indicated that Streptococcus pneumoniae (30% [I2 = 56% p < 0.01]), Haemophilus influenza type b (15% [I2 = 82.75% p < 0.001]), coagulase negative staphylococci (CoNS) (14% [I2 = 60.5% p < 0.06]), and Neisseria meningitidis (13% [I2 = 74.16% p < 0.001]) were the most common cause of acute bacterial meningitis among meningitis cases in Iran. Notably, high frequency rates of nosocomial meningitis pathogens were detected in the present analysis. Conclusions It was magnificently attained that the majority of cases for bacterial meningitis in Iran could be avertable by public immunization schemes and by preventive care to inhibit the broadening of hospital acquired pathogens.